Direct medical costs and healthcare resource utilization of treating patients with two clinical subtypes of axial spondyloarthritis in Colombia (2022)
Objectives: This study aimed to calculate the healthcare resource utilization and direct medical costs in patients with 2 subtypes of axial spondyloarthritis (axSpA) in a rheumatic care center in Colombia. Methods: This is a retrospective cost-of-illness study. Patients with at least 1 medical consultation associated with an axSpA diagnosis between October 2018 and October 2019 were identified. Patients were classified as having radiographic (r-axSpA) or nonradiographic axSpA (nr-axSpA). Direct medical costs were calculated in Colombian pesos and expressed in American dollars using an exchange rate of 3263 Colombian pesos = 1 US dollar ($). Predictors of total direct costs were identified using a generalized linear model with gamma distribution and log-link. Results: A total of 162 patients with a mean age of 49.6 years (6 13.7) were included in the study. Among these, 147 (90.7%) were considered as having r-axSpA and 15 (9.3%) nr-axSpA, with mean costs of $6600 (6 6203) and $843 (6 1135), respectively (P , .001). The total direct mean cost was calculated at $6067 (6 6144) per patient. Medication costs were the main driver of total costs (97.6%, $5921), with biologic disease-modifying antirheumatic drugs accounting for nearly 92.0% ($5582) of these costs. Rheumatologist (100%) and physiatrist (64.2%) visits were the most frequently used medical service. Conclusions: The economic burden associated with axSpA in the Colombian setting is substantial. There is a significant difference in direct medical costs between the r-axSpA and the nr-axSpA. Health policies aimed at the comprehensive management of nr-axSpA would have an important role in the reduction of the associated direct medical costs.